(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2020)
The study was conducted to explore tree species diversity of Renikhayong para Village Common Forest (VCF) of Bandarban hill district. Stratified random sampling was carried out to assess the tree species diversity of the VCF. Renikhayong Para VCF with an area of 40 acres of land has more than 85 tree species belonging to 31 families, where Euphorbiaceae family was dominant containing 11 species followed by Rubiaceae (7 species), Moraceae (7 species), Meliaceae (5 species), Mimosaceae (5 species), Combretaceae (4 species), Lauraceae (4 species) and Anacardiaceae (3 species). Dominant tree species was Grewia nervosa. Renikhayong para VCF has diverse floristic resources that are known from the Shannon-Wiener’s diversity index (4.007), Simpson’s diversity index (0.028), Margalef’s richness index (13.21) and Species evenness index (0.90). However, number of species and number of individuals both were highest in the height range of 5 - <10 m. Similar trend was observed in dbh classes. Number of individuals were highest in dbh range of 5 - <15 cm and the lowest in ≥ 55 cm. The results depict the presence of maximum small trees in the VCF and decreasing the number of trees with the increase of tree height (m) and dbh (cm). Presence of diverse tree species and diversity indices indicate the importance and potential of the VCF for conservation and sustainable use. J. Biodivers. Conserv. Bioresour. Manag. 2019, 5(2): 115-126